If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3)(3x + 5) = 0 Reorder the terms: (-3 + 4x)(3x + 5) = 0 Reorder the terms: (-3 + 4x)(5 + 3x) = 0 Multiply (-3 + 4x) * (5 + 3x) (-3(5 + 3x) + 4x * (5 + 3x)) = 0 ((5 * -3 + 3x * -3) + 4x * (5 + 3x)) = 0 ((-15 + -9x) + 4x * (5 + 3x)) = 0 (-15 + -9x + (5 * 4x + 3x * 4x)) = 0 (-15 + -9x + (20x + 12x2)) = 0 Combine like terms: -9x + 20x = 11x (-15 + 11x + 12x2) = 0 Solving -15 + 11x + 12x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -3x)(3 + -4x) = 0Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(3 + -4x)' equal to zero and attempt to solve: Simplifying 3 + -4x = 0 Solving 3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 0 + -3 -4x = 0 + -3 Combine like terms: 0 + -3 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75Solution
x = {-1.666666667, 0.75}
| 5x+20=65 | | 3m+2n+2= | | 8p^2=-56p | | 4*6*x+(6x*5x)= | | 3[y+4]=-9 | | 7(3t-2)=28 | | 4(2y+3)=52 | | 5(y-2)=60 | | 5k-2=33 | | 3(x+6)=6(2+y) | | 3x+8=-4x-6 | | 4(n+9)-3(2+n)= | | 5(6+n)-2(n-2)= | | 6r+2(r+4)= | | 2+3xy-4xy+6= | | (2x+6)(5x-13)=0 | | x-1.6x-2.6=0.6x+2.2 | | 2(2-x)-4(2x-1)=4(x-1)-3(2x-3) | | 0.33333+x=-0.53333 | | 4.8x+2=3.8x | | 4.8-2=3.8x | | 0.6w+-1w= | | 0.7-(x-2.5)=10.5 | | 13-(-4-x)=1 | | 5.3+9.2x=7.4-8.8 | | 2x+x-12=0 | | 2.3x+6.8=3.94x-3.44 | | 4*(2+x)-2*(x+3)= | | 4d+4=3d+9 | | -(2x-5)=4(x+2) | | 2+3x-(2x+3)= | | 8x+7=2x+10 |